Exploring The Views Of Healthcare Practitioners On Postnatal Mental Illness Screening Among Malaysian Women - Siti Roshaidai Mohd Arifin; Siti Aishah Daud; Nur Liyana Shahmi Ruslan; Khadijah Hasanah Abang Abdullah; Nurul Ain Hidayah Abas; Rohayah Husain; Karimah Hanim Abd Aziz; Ramli Musa; Fathima Begum Syed Mohideen; Asma Perveen; Khairi Che Mat; Izazol Idris (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by MyCite